Analysis of Perceptions of University Students in Southern Thailand towards Jawi Script: A Case Study of Students at the Syeikh Daud Al-Fathani Islamic College, Yala, Thailand - Song, Muhammad Alee (Melayu: Jurnal Antarabangsa Dunia Melayu, 2024)
Jawi script is the main medium of Malay language writing in Southern Thailand, specifically Yala, Pattani, Narathiwat, Satun, and several other districts in the Songkhla region that were previously part of the Malay Sultanates of Patani and Kedah-Perlis before their cession to the Thai national territory based on the Anglo-Siamese Agreement of 1909. This study aims to identify the perceptions of university (IPT) students in Southern Thailand towards Jawi script. This study uses a quantitative approach as data collection medium through survey research design via a questionnaire involving 30 IPT first-degree students at the Syeikh Daud alFathani Islamic College (KISDA) in Yala, Southern Thailand. The data obtained from the questionnaire were analysed using descriptive statistics. The findings show that the university students have a positive perception of the Jawi script. The ability to use Jawi script is important as a symbol of Patani Malay identity, which dictates a high perceived value. This study somewhat illustrates the importance of Jawi script among the young Malay generation and its role as a marker of Patani Malay national identity. Full text : PDF